Escape From X-Chromosome Inactivation: An Evolutionary Perspective - Posynick, Bronwyn J.; Brown, Carolyn J. (Frontiers in Cell and Developmental Biology, 2019)
Sex chromosomes originate as a pair of homologus autosomes that then follow a general pattern of divergence. This is evident in mammalian sex chromosomes, which have undergone stepwise recombination suppression events that left footprints of evolutionary strata on the X chromosome. The loss of genes on the Y chromosome led to Ohno’s hypothesis of dosage compensation between X-hemizygous males and the autosomes, as well as dosage equivalence between XY males and XX females. Evidence for dosage compensation is inconsistent and largely dependent on the filtering of genes for consideration. Dosage equivalence is achieved through X-chromosome inactivation (XCI), which transcriptionally silences all but one X chromosome in each female cell. Notably, 15-30% of human X-linked genes escape inactivation. There are multiple evolutionary pathways that may lead to a gene escaping XCI, including surviving Y chromosome homology, lack of dosage sensitivity, female advantage, and lack of accumulation of silencing elements. The conservation of escape genes across multiple species and the ability of the mouse inactive X to recapitulate human escape status both suggest that escape from XCI is controlled by conserved processes. Delineation of the elements involved in escape is progressing, but mechanistic understanding of how they interact to allow escape from XCI is still lacking. Although increasingly well-studied in humans and mice, nontrivial challenges to studying escape have impeded progress in other species. Mouse models that can dissect the role of the sex chromosomes distinct from sex of the organism reveal an important contribution for escape genes to multiple diseases. In humans, with their elevated number of escape genes, the phenotypic consequences of sex chromosome aneuplodies and sexual dimorphism in disease both highlight the importance of escape genes.